RESPONSIVE GOVERNANCE APLIKASI SISTEM ADMINISTRASI KENDARAAN PAJAK ONLINE (SAKPOLE) SAMSAT KOTA SEMARANG II - Annisa Putri Fernanda; Retno Sunu Astuti; Amni Zarkasyi Rahman (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
This research analyzes the responsiveness of SAMSAT Semarang City II and identifies inhibiting factors. It is driven by public complaints regarding the administration services provided by SAMSAT. The introduction of the SAKPOLE application aims to streamline motor vehicle administration and enable public complaint submission. Aligned with UNDP's principles of good governance, the study emphasizes transparency, accountability, participation, and coordination. The SAKPOLE app offers a quick and flexible resolution for public complaints. Descriptive qualitative methods, including interviews, documentation, and observation, are used for data collection. Primary data is obtained from SAMSAT and the public, while secondary data includes documentation, news, reports, laws, and the SAKPOLE app. Data validity is ensured through source triangulation. Findings show that the SAKPOLE platform, public participation, competent SAMSAT staff, and effective complaint handling processes facilitate responsive governance. Inhibiting factors include incomplete complaint information and a lack of human resources. To enhance the SAKPOLE app, clear complaint information, adherence to procedures, and staff training are recommended.